Analysis of Fossil Pollen Record from the Late Holocene in the Turkish Highland (Middle Taurus,Turkey) - Özalp, İpek and Caner, Hülya and Karlıoğlu Kılıç, Nurgül and Avcı, Meral (Ecological Questions, 2017)
In this study, we have investigated changes of vegetation in the Mediterranean Region of Turkey approximately for the last 5000 years using pollen analysis . There were some differences in the past vegetation, but principally vegetation structure has shown similarity with the modern one. Main difference appeared with the existence of Betula.